Research on anaerobically treated organic waste suitability for soil fertilisation - Kvasauskas, Mindaugas; Baltrėnas, Pranas (Journal of Environmental Engineering and Landscape Management, 2009)
One of the most promising methods to convert organic waste into alternative energy and still obtain fertiliser is anaerobic digestion of waste in bioreactors. To evaluate the suitability of biodegraded organic waste for soil fertilisation, an experiment aimed at determining the amount of total nitrogen, total phosphorus and heavy metals contained in this waste and testing of its pH was carried out. The following organic waste was used for the research: sewage sludge from wastewater treatment plants, fruit and vegetable waste, hen manure, piggery slurry and grain. The biggest contents of nitrogen and phosphorus were determined in anaerobically treated swine manure and therefore, it was found the most suitable organic fertiliser to remediate exhausted soils and used‐up areas. Treated swine manure contains 8.27 mg/l of nitrogen and 293.1 mg/l of phosphorus. The biggest contents of heavy metals were determined in anaerobically treated sewage sludge from wastewater plants. The concentration of chromium amounts to 1.53 mg/kg, that of zinc ‐21.28 mg/kg, manganese ‐ 50.03 mg/kg, lead ‐ 10.46 mg/kg, copper ‐ 50.48 mg/kg and nickel ‐ 12.88 mg/kg. In none of the researched cases heavy metal concentrations in treated organic waste exceeded the maximum permissible concentration (MPC). Anaerobically treated swine manure and sewage sludge with the highest pH indicators, 7 and 7.1, respectively, are most suitable for the fertilisation of acid soils. It could be proposed that digested pig manure is best soil fertilizer from all investigated organic wastes when biogenic elements, heavy metals and pH were measured. Anaerobiškai perdirbtų organinių atliekų tinkamumo dirvožemiui tręšti tyrimai Santrauka. Vienas iš perspektyviausių metodų organines atliekas paversti alternatyvia energija ir dar gauti trąšą – anaerobinis atliekų skaidymas bioreaktoriuose. Biologiškai suskaidytų organinių atliekų tinkamumas panaudoti dirvai tręšti įvertintas atlikus eksperimentą. Jo tikslas buvo ištirti bendrojo azoto, bendrojo fosforo, sunkiųjų metalų kiekius šiose atliekose bei nustatyti jų pH. Tyrimams naudotos organinės atliekos: nuotekų valymo dumblas, vaisių ir daržovių atliekos, vištų mėšlas, kiaulidžių srutos ir žlaugtas. Nustatyta, kad daugiausia azoto ir fosforo turi anaerobiškai perdirbtas kiaulių mėšlas, todėl jis tinkamiausias kaip organinė trąša labiausiai nualintiems dirvožemiams bei išeksploatuotiems plotams rekultivuoti. Azoto perdirbtame kiaulių mėšle yra 8,27 mg/l, fosforo – 293,1 mg/l. Didžiausi sunkiųjų metalų kiekiai nustatyti anaerobiškai perdirbtame nuotekų valyklos dumble. Chromo koncentracija siekia 1,53 mg/kg, cinko – 21,28 mg/kg, mangano – 50,03 mg/kg, švino – 10,46 mg/kg, vario – 50,48 mg/kg, nikelio – 12,88 mg/kg. Nė vienu iš tirtų atvejų sunkiųjų metalų koncentracijos perdirbtose organinėse atliekose neviršijo DLK. Labiausiai rūgštiesiems dirvožemiams tręšti tinka anaerobiškai perdirbtas kiaulių mėšlas ir nuotekų valymo dumblas, kurių pH rodiklis didžiausias – siekia atitinkamai 7 ir 7,1. Įvertinus biogeninių elementų ir sunkiųjų metalų kiekį bei pH, galima teigti, kad dirvai tręšti iš tirtųjų organinių atliekų tinkamiausias yra kiaulių mėšlas. Reikšminiai žodžiai: dirvožemis, tręšimas, bendrasis azotas, bendrasis fosforas, sunkieji metalai, pH, organinės atliekos. Исследование пригодности анаэробно переработанных органических отходов для удобрения почв Резюме. Одним из наиболее перспективных методов преобразования органических отходов в альтернативную энергию и удобрения является анаэробное сбраживание отходов в биореакторах. Для оценки пригодности внесения в почву биологически переработанных органических отходов в виде удобрений проводился эксперимент с целью определения суммы содержащихся в отходах общего азота, общего фосфора, тяжелых металлов и рН. Для исследований в качестве органических отходов использовался ил сточных вод из очистных сооружений, фруктово-овощные отходы, куриный помет, навоз и навозная жижа. Наибольшее содержание азота и фосфора было определено в анаэробно переработанном свином навозе, поэтому он наиболее приемлем в качестве органического удобрения для восстановления и рекультивации почв. Обработанный свиной навоз содержит 8,27 мг/л азота и 293,1 мг/л фосфора. Наибольшее содержание тяжелых металлов было установлено в анаэробно переработанном иле из сточных вод предприятий. Концентрация хрома в нем составляла 1,53 мг/кг, цинка – 21,28 мг/кг, марганца – 50,03 мг/кг, свинца – 10,46 мг/кг, меди – 50,48 мг/кг, никеля – 12,88 мг/кг. Ни в одном из исследованных случаев концентрации тяжелых металлов в переработанных органических отходах не превышали максимально допустимых концентраций (ПДК). Для удобрения кислых почв наиболее приемлем анаэробно переработанный свиной навоз и ил стоков из очистителей, содержащие высший показатель pH (соответственно 7 и 7,1). На основании полученных величин биогенных элементов, тяжелых металлов и pH можно утверждать, что из всех исследованных органических отходов наиболее пригоден для удобрения почв свиной навоз. Ключевые слова: почва, удобрения, общий азот, общий фосфор, тяжелые металлы, рН, органические отходы. First Published Online: 14 Oct 2010